The effect of background argon gas pressure on parameters of plasma produced by Dc- glow discharge - Jawad, Mohammed H.; Abdulameer, Mohammed R. (Iraqi Journal of Science, 2023)
Non-thermal plasmas have become popular as plasma technology has advanced in various fields, including waste management, aerospace technology, and medicinal applications. They can be used to replace combustion fuels in stationary hall motors and need little effort to keep running for longer periods of time. To improve overall system performance, non-reactive gases such as )Xe, Ar, and Kr) are utilized in pure or mixed form to generate plasma. Since DC glow discharge is a fundamental topic of importance, these gases have been researched. The paper concentrates on 2-D modeling and simulation. DC glow-discharge tubes are utilized with argon gas to create plasma and learn about its properties. The magnitude of the electron density, increases with rising pressure, whilst the rest of the parameters gradually decrease with increasing pressure